Program Pengawasan dalam Pengembangan Satuan Pendidikan - Zulkarnaen Zulkarnaen (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
Education occupies a central position in the development of the nation's youth which should be given special attention, one of which is monitoring. Supervision functions in the running of the program according to regulations, is specific, clear, can be measured in terms of achievement, by various conditions in the school with the needs and circumstances of the school and a clear target time for achieving each step of the activity. In preparing a monitoring program, you can start by conducting a SWOT analysis (Strength, Weakness, Opportunities, and Threats). This SWOT analysis is intended to identify the strengths, weaknesses, opportunities, and threats that exist in schools in the target area that will be improved in quality.The educational unit supervision program is in the form of a series of activities that will be carried out to achieve the supervision objectives. The supervision program is prepared to provide an explanation of the purpose of supervision, the objectives of supervision, the people involved, how the supervision process is carried out, and when the supervision is carried out.